Off-stoichiometric nickel cobaltite nanoparticles: thermal stability, magnetization, and neutron diffraction studies - Verma, Seema; Kumar, Amit; Pravarthana, D.; Deshpande, Aparna; Ogale, Satishchandra B.; Yusuf, S. M. (Journal of Physical Chemistry C, 2014)
In the present investigation, we report a detailed examination of the effect of off-stoichiometry introduced in NiCo2O4 by adding excess cobalt. Thus, we compare and analyze the structural and magnetic properties of the Ni075Co2.25O4 and NiCo2O4 cubic systems. A low temperature combustion method was utilized to synthesize stoichiometric (NiCo2O4) and off-stoichiometric (Ni0.75Co2.25O4) nanoparticles on a large scale. The X-ray diffraction pattern for the sample annealed at high temperature (773 K) shows the presence of a much less intense NiO phase (similar to 2-5%) in Ni0.75Co2.25O4 as compared to that in the case of NiCo2O4 sample (similar to 15-20%). The Ni 2p and Co 2p XPS spectra reveal the coexistence of Ni2+, Ni3+, Co2+, and Co3+ species on the surface of both the NiCo2O4 and Ni0.75Co2.23O4 samples in differing proportions. In addition to the basic magnetic characterizations using PPMS, these were also analyzed by neutron diffraction. The off-stoichiometric Ni0.75Co2.25O4 sample shows an interesting magnetic phase conversion from frustrated dipolar system to an enhanced magnetic ordering upon annealing. Local moments on the lattice sites of NiCo2O4 and Ni0.75Co2.25O4 samples are further compared by neutron diffraction confirming stronger ordered moments and enhanced structural and thermal stability for the Ni0.75Co2.25O4 sample.